Optimisation of the RT-PCR detection of immunomagnetically enriched carcinoma cells - Walsh David CA; Stephenson Sally-Anne; Raynor Michael; Pittman Kenneth B; Dobrovic Alexander (BMC Cancer, 2002)
Abstract Background Immunomagnetic enrichment followed by RT-PCR (immunobead RT-PCR) is an efficient methodology to identify disseminated carcinoma cells in the blood and bone marrow. The RT-PCR assays must be both specific for the tumor cells and sufficiently sensitive to enable detection of single tumor cells. We have developed a method to test RT-PCR assays for any cancer. This has been investigated using a panel of RT-PCR markers suitable for the detection of breast cancer cells. Methods In the assay, a single cell line-derived tumor cell is added to 100 peripheral blood mononuclear cells (PBMNCs) after which mRNA is isolated and reverse transcribed for RT-PCR analysis. PBMNCs without added tumor cells are used as specificity controls. The previously studied markers epidermal growth factor receptor (EGFR), mammaglobin 1 (MGB1), epithelial cell adhesion molecule (EpCAM/TACSTD1), mucin 1 (MUC1), carcinoembryonic antigen (CEA) were tested. Two new epithelial-specific markers ELF3 and EphB4 were also tested. Results MUC1 was unsuitable as strong amplification was detected in 100 cell PBMNC controls. Expression of ELF3, EphB4, EpCAM, EGFR, CEA and MGB1 was found to be both specific for the tumor cell, as demonstrated by the absence of a signal in most 100 cell PBMNC controls, and sensitive enough to detect a single tumor cell in 100 PBMNCs using a single round of RT-PCR. Conclusions ELF3, EphB4, EpCAM, EGFR, CEA and MGB1 are appropriate RT-PCR markers for use in a marker panel to detect disseminated breast cancer cells after immunomagnetic enrichment.